New chiral 1,2-aminoalcohols derived from biomass and their application in enantioselective diethyl zinc additions - Zanardi, Maria Marta (2014)
A convenient procedure for the preparation of chiral 1,2-aminoalcohols starting from levoglucosenone, a biomass derivative, is described. The 1,2-aminoalcohols, bearing primary, secondary, and tertiary amino groups, were tested as chiral catalysts in the asymmetric addition of diethyl zinc to benzaldehyde.